2012
DOI: 10.1007/s00216-012-5728-x
|View full text |Cite
|
Sign up to set email alerts
|

Direct analysis in real time mass spectrometry combined with single-drop liquid–liquid–liquid microextraction for the rapid analysis of multiple phytohormones in fruit juice

Abstract: A rapid, simple, and efficient method for the fast determination of multiple phytohormones was developed in this work, based on single-drop liquid-liquid-liquid microextraction (SD-LLLME) combined with direct analysis in real-time mass spectrometry (DART-MS). Six phytohormones--indole-3-acetic acid (IAA), indole-3-butyric acid (IBA), jasmonic acid (JA), salicylic acid (SA), abscisic acid (ABA), and gibberellin A(3) (GA(3))--were analyzed simultaneously using this method, and the conditions employed for DART-MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 39 publications
1
37
0
Order By: Relevance
“…In the traditional methods described in the Introduction section, the ABA sample preparation from plant materials needs one or more times of each of the extraction, purification and solvent concentration steps [6,7,11,12,[15][16][17][18]. These multiple-step methods had low recovery rate, used large volume of solvent, and is time-consuming.…”
Section: Analysis Of Aba In Peanut Leaves During Drought Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…In the traditional methods described in the Introduction section, the ABA sample preparation from plant materials needs one or more times of each of the extraction, purification and solvent concentration steps [6,7,11,12,[15][16][17][18]. These multiple-step methods had low recovery rate, used large volume of solvent, and is time-consuming.…”
Section: Analysis Of Aba In Peanut Leaves During Drought Stressmentioning
confidence: 99%
“…Recently, some new techniques for sample preparation and enrichment of the ultra trace compound in plants have been developed based on the solid-phase extraction (SPE) and liquid-liquid fractionation (LLF), such as solid phase microextraction [9], magnetic solid phase extraction (MSPE) [6], dispersive solidphase extraction (DSPE) [15], liquid-liquid-liquid microextraction (LLLME) [16,17], dispersive liquid-liquid microextraction (DLLME) http://dx.doi.org/10.1016/j.jchromb.2015.08.033 1570-0232/© 2015 Elsevier B.V. All rights reserved. [18], etc.…”
Section: Introductionmentioning
confidence: 99%
“…The standard saccharide samples were dissolved in a methanol-water mixture, and a standard melting point capillary tube was dipped into the solution and then placed in the helium stream of the DART ion source [182]. Six phytohormones were analyzed simultaneously using a DART ion source and single drop liquid-liquid microextraction in three different kinds of freshly prepared fruit juice in less than 30 min [183]. Another study on fruit juice using a DART ion source also demonstrated high-throughput screening and detection of polysorbate 20/80 micelles in apple juice [184].…”
Section: Applications Of Dart-msmentioning
confidence: 99%
“…Until now, several papers have been published describing various DART applications including rapid analysis of various (target) substances occurring in foodstuffs and food crops [29,[34][35][36][37][38][39][40], but only a limited number of papers have been focused on metabolomics-based studies based on non-target approach [32,33,[41][42][43].…”
Section: Introductionmentioning
confidence: 99%